Profil Perkembangan Bakat Khusus Peserta Didik di SMP Negeri 1 Siberut Selatan Kabupaten Kepulauan Mentawai - Julianna Sagulu (STKIP PGRI Sumatera Barat, 2021)
: This reserch is motivated by the presence of student who are less able to understand and remember the lessons given by the teacher, less able to speak indonesian, less able to calculate mathematic lessons, low grade 1 raport card, lazy to participate in school activities, and lack of support, motivation from parent. The purpose of this research is to descibe: 1. Development of special academic talents, 2. Artistic talents, 3. Kinesthetic/psychomotor talents, 4. Social talents. This research was conducted using quantitative descriptive methods. The study pupolation was 150 students. The technique of taking proportional random sampling is 60 students. The research data were obtained through questionnaires and processed using percentage teachiques.Based on the results of research conducted at SMP Negeri 1 South Siberut, Mentawai Islands Regency, the following conclusions can be drawn: 1. Talent for working numbers (Numerical) is in the category of many criteria as many as 5 people (71,66%), 2. Talents in using laguage there are very many categories as many as 35 people (58,33%), 3. Talents are able to arrange and are greatly admired in the category quite a lot as many as 14 people (23,33%), 4. The talents to create songs in 30 minutes is quite a lot category as many as 27 people (45%). The results of this study are recommended to the supervisor/counselor to assist students in developing the special talents of students at SMP negeri 1 South, Mentwai Island Regency. Key word: Profile, Development, Special Talents